A highly durable catalyst system for hydrogen production from dimethyl ether - Stöber, Robert; Seidl, Franziska; Hoffmann, Emanuel; Wasserscheid, Peter; Schühle, Patrick (Sustainable Energy & Fuels, 2024)
Dimethyl ether (DME) is a promising vector for the transportation of hydrogen over long distances and from point to point. However, a major challenge to the large-scale application of this technology has been the notoriously unstable nature of the so far applied steam reforming catalysts. In this paper, we describe a physical mixture of γ-Al2O3 and zirconia-supported In2O3 as a highly stable catalyst system for the steam reforming of dimethyl ether (SRD). Our work shows that the use of 3 wt% In2O3 on ZrO2 provides the highest activity and hydrogen yield in the temperature range of 350-400 °C. In addition, the developed catalyst system shows excellent stability over an operating time of 425 h with a DME conversion of nearly 100% and a hydrogen yield of about 90%. To maximize the hydrogen yield further, a water-gas shift reactor was operated downstream of the SRD reactor, but at lower temperatures, to reduce the CO concentration in the product mixture to its thermodynamic equilibrium concentration. This synergetic operation led to a maximum hydrogen yield of 95%.
CRIS-Team Scopus Importer:2024-05-03

A Highly Stable Bimetallic Transition Metal Phosphide Catalyst for Selective Dehydrogenation of n-Heptane - Stöber, Robert; Mai, Florian; Oshin, Oshin; Körner, Andreas; Hutzler, Andreas; Schühle, Patrick (ChemCatChem, 2022)
In this work, we demonstrate RuP2-MoP catalysts being highly stable and selective for the dehydrogenation of long-chain alkanes like n-heptane. Compared to a monometallic MoP catalyst, the bimetallic system substantially increases n-heptene selectivity from 40 % towards 80 %. This effect can be traced back to a reduced surface acidity, suppressing the competitive hydrogenolysis reaction. The active transition metal phosphide is, furthermore, compared to its phosphorous-free RuMo-counterpart. As revealed by STEM-EDX investigations, incorporation of phosphorous results in the formation of separated metal phosphide clusters instead of an intermetallic alloy. In the dehydrogenation of n-heptane the phosphorous modification clearly avoids catalyst deactivation and maintains the high n-heptene selectivity. X-ray diffraction, elemental analysis and STEM-EDX further reveal that catalyst coking and the formation of less active molybdenum carbide phases is effectively suppressed by phosphorous incorporation, making RuP2-MoP an attractive system for selective dehydrogenation of long-chain alkanes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Alkane dehydrogenation; Coking resistance; Heterogeneous catalysis; Molybdenum catalyst; Transition metal phosphides

Application of In2O3-catalysts for Slurry Phase Hydrogenation of CO2 to Methanol: Influence of reaction conditions, support and catalyst preparation - Schühle, Patrick; Reichenberger, S.; Marzun, G.; Albert, Jakob (DGMK Tagungsbericht, 2019)
To reduce greenhouse gas emissions the development of novel storage and transport technologies for renewable produced electrical power is necessary. In comparison to conventional energy, renewables are highly dependent on the availability of primary energy sources like wind and sunlight. One concept to overcome this challenge is to convert electrical to chemical energy, e.g. by electrolysis of water to hydrogen and oxygen in an electrolysis cell. Yet storage and transport of hydrogen is a challenging task requiring the subsequent conversion to base chemicals like methanol. Due to the deactivation of the industrial Cu/ZnO/Al2O3-catalysts by stoichiometrically produced water [1], novel water resistant catalysts for the CO2 hydrogenation to methanol are required. Recently, it has been shown that heterogeneous In2O3-catalysts supported on semiconductor metal oxides presents a promising alternative [2], but require further catalyst development. In this work we follow two different synthesis approaches, namely wet-chemical impregnation and laser-based catalyst preparation. The latter represents a novel technique to individually study the catalytic activity in terms of nanoparticle purity, functional properties (size, morphology, oxidation state) and support properties (e.g. defect densities) [3]. Nanoparticles are synthesized by scalable pulsed laser ablation in a liquid under surfactant-free conditions and subsequent adsorption in chosen weight loading, onto various oxidic support materials. Due to subsequent processing, nanoparticle properties (e.g. nanoparticle size) are adjusted independently of the nanoparticle load or the used support [3]. Furthermore, the gained nanocatalyst is active without high temperature calcination further maintaining preadjusted support properties (e.g. defect structure of dopant distribution). To quantify the activity of the catalysts for methanol synthesis a slurry reactor with suspended catalyst in a high boiling liquid phase was used. Advantages of this concept are the applicability of catalysts in the size of nanometers without inducing high pressure drops. To examine the influence of the catalyst morphology on the catalytic performance, several analytical techniques were used. The Indium-loading of the catalyst was checked by ICP-OES. BET-sorption measurements and CO2-TPD were applied for the characterization of the catalyst supports concerning their total surface area and CO2 binding capacity. Via XPS measurement the oxidation state of the Indium-and Zirconia-species were analysed before and after the reaction. Furthermore, the catalyst surface was examined by electron microscopy and XRD.
CRIS-Team Scopus Importer:2021-04-20

Burner-heated dehydrogenation of a liquid organic hydrogen carrier (LOHC) system - Bollmann, Jonas; Mitländer, Kerstin; Beck, Dominik; Schühle, Patrick; Bauer, Florian; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
For a hydrogen-based economy, safe and efficient hydrogen storage is essential. Compared to other chemical hydrogen storage technologies, such as ammonia or methanol, liquid organic hydrogen carrier (LOHC) systems allow for a reversible storage of hydrogen while being easy to handle in a diesel-like manner. In our contribution, we describe for the first time the successful utilization of the exhaust gas enthalpy of a porous media burner to directly supply the dehydrogenation heat for a kW-scale dehydrogenation of the hydrogen-rich LOHC compound perhydro dibenzyltoluene (H18-DBT). Our setup demonstrates the dynamics of the dehydrogenation unit at a realized maximum hydrogen power of 3.9 kWth, based on the lower heating value of the released hydrogen. For the intended applications with fluctuating hydrogen demand, e.g. a hydrogen refueling station (HRS) or stationary heating in buildings, a dynamic hydrogen supply from LOHC is important. Methane, e.g. from a biogas plant, is utilized in our scenario as a fuel source for the burner. Hydrogen is released within 30 min after cold start of the system. The dehydrogenation unit exhibits a power density relative to the reactor volume of about 0.5 kWtherm l−1 based on the lower heating value of the hydrogen and a catalyst productivity of up to 0.65 gH2 gPt−1 min−1 for hydrogen release from H18-DBT. An analysis of the by-products and reaction intermediates shows low by-product formation (e.g. maximum 0.6 wt.-% for high boilers and 0.9 wt.- % for low boilers) and uniform distribution of intermediates after the reaction. Thus, a relatively homogeneous temperature distribution and a uniform LOHC flow in the reaction zone can be assumed. Our findings illustrate the dynamics (heating rates of about 10 K min−1) and performance of direct heating of a release unit with a burner and represent a significant step towards LOHC-based hydrogen provisioning systems at technically relevant scales.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Dehydrogenation; Dynamic heat supply; Hydrogen storage; LOHC; Porous media burner

Chloroorganic impurities in technical-grade benzyltoluene – Influence on its use as LOHC compound and removal strategies - Henseler, J.; Rullo, F.; Mitländer, Kerstin; Johner, N.; Wolf, P.; Schühle, Patrick; Geißelbrecht, M.; Wasserscheid, P. (International Journal of Hydrogen Energy, 2024)
The benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) LOHC system is very attractive for large-scale hydrogen storage and transportation applications due to its fuel-like handling and excellent technical availability. H0-BT is applied in industrial quantities since the 1960′ies as heat trafer fluid and is technically produced by a Friedel-Crafts alkylation of chlorobenzene and toluene. However, the current production route leads to minor impurities of chloroorganic compounds in technical H0-BT that were found to severely harm the performance in the catalytic hydrogenation to H12-BT, i.e. in the hydrogen charging process of the respective LOHC storage cycle. Our contribution deals with three aspects of this practically highly relevant topic: a) It discloses the previously unknown chemical structure of the relevant chloroorganic impurities; b) it develops a process for their removal by adsorption and/or hydrodechlorination using a commercial Ni/SiO2–Al2O3 material, and c) it determines the performance difference of the so-purified H0-BT samples and H0-BT samples containing the relevant chloroorganic compounds in the catalytic hydrogenation of H0-BT to H12-BT.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Benzyltoluene; Catalyst poisoning; Chloroorganic compounds; Hydrodechlorination; Hydrogenation; Impurities; LOHC

CO2-hydrogenation to methanol using indium-based catalysts in slurry and fixed-bed reactors - Schühle, Patrick (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2021)

Continuous Dehydrogenation of Perhydro Benzyltoluene in a Catalytic Finned Tube Reactor - Ellert, Abelina; Schmacks, Michael; Braun, Mikkel J.; Piccirilli, Luca; Janssens, Ton V.W.; Wasserscheid, Peter; Schühle, Patrick (Industrial & Engineering Chemistry Research, 2025)
Storage and transport of hydrogen by charging liquid organic hydrogen carriers (LOHC) has emerged as a promising technology, as these LOHC can be handled within the existing fuel infrastructure. For the release of hydrogen from LOHC on board heavy-duty vehicles, coated reactor systems are advantageous, as the heat transfer to the catalyst is fast and efficient and the immobilized catalyst is protected from movement and abrasion in the reactor. However, the challenge is to provide a sufficient surface area for the catalytic coating, which is required to achieve high volumetric power densities. We here introduce a novel coated finned tube reactor concept for the dehydrogenation of the LOHC compound perhydro benzyltoluene (H12-BT). The reactor consists of a series of vertically arranged stainless-steel finned tubes, coated with a catalytically active layer (Pt-S/Al2O3). This results in a large catalytic surface area per reactor volume. Stable coatings have been obtained through dip-coating an Al2O3 slurry onto the finned tubes followed by impregnation with a platinum sulfite acid solution. The finned tubes are individually heated from the inside, allowing for a well-defined and manageable temperature distribution and fast responses under dynamic conditions (e.g., during vehicle start-up). The finned tube reactor exhibits plug flow reactor characteristics with increasing degrees of dehydrogenation (DoDh) in the flow direction. We have achieved a power density of more than 1 kW L-1 reaction volume at degrees of dehydrogenation above 70%. With this performance, the finned tube reactor concept shows high potential compared to state-of-the-art reactor concepts. By combining the new reactor type with a simple active carbon filter, PEM-fuel cell grade hydrogen (CO content <0.1 ppm, methane <70 ppm) was produced. This work demonstrates the finned tube reactor as an attractive concept for efficient hydrogen release from LOHC systems.
CRIS-Team Scopus Importer:2025-02-17

Continuous (hydro-)dechlorination of aromatic chloride compounds in benzyltoluene - Mitländer, Kerstin; Henseler, J.; Rullo, F.; Nathrath, Phillip; Geißelbrecht, M.; Wasserscheid, Peter; Schühle, Patrick (International Journal of Hydrogen Energy, 2025)
Benzyltoluene is an attractive liquid organic hydrogen carrier (LOHC) compound but needs to be purified after its technical synthesis to remove chloride impurities that would harm the Pt-based hydrogenation and dehydrogenation catalysts used for the reversible LOHC loading and unloading with hydrogen. For this purpose the dechlorination of chlorobenzyltoluene in a benzyltoluene matrix was studied in a continuously operated trickle bed reactor using a commercially available nickel catalyst. The results indicate that the removal of chlorobenzyltoluene is mainly adsorption based. Rapid aging experiments with purposely added chloroaromatic compounds (chlorobenzene and chloronaphthalene) in quantities of up to 9000 ppm suggest that high chloroaromatic loadings lead to reduced dechlorination activity due to a rapid blocking of active sites. The dechlorination capacity per gram of the used catalyst material was determined to be in the range of 2 kg of technical benzyltoluene.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Benzyltoluene; Chloroaromatics; Chlorobenzene; Dechlorination; LOHC

Controlled doping of carbon catalyst supports by atomic replacement via gasification-assisted heteroatom doping - Herold, Felix; Imhof, Timo; Roumeliotis, Paul; Schühle, Patrick; Ledendecker, Marc; Rønning, Magnus (Carbon, 2023)
Due to a set of unique properties, carbon materials are applied as supports for metal-based catalysts in a wide variety of established and emerging (electro-)catalytical transformations. By introducing heteroatoms such as N, S and P into carbon supports, metal-support interactions can be tuned, enabling an optimization of catalyst performance in terms of activity, selectivity and stability. However, the exact impact of carbon heteroatom doping on catalyst performance remains often poorly understood, as the effects are inseparable from the clustered influence of other support properties such as texture and nanostructure. In this context, we present gasification-assisted heteroatom doping (GAHD) as a novel, broadly applicable post synthesis approach to exchange carbon surface atoms against heteroatoms while retaining the properties of the parental carbon. Employing GAHD, N, S and P doping of carbons with widely varying properties could be achieved, allowing, for example, incorporation of up to 13.1 wt-% S into an activated carbon at a change of specific surface area of only 4.4%. As a proof-of-concept, comparable N, S and P doped carbon nanofiber supports were used to prepare Pt-based electrocatalysts for the oxygen reduction reaction and probe the influence of the heteroatom dopants on their stability by accelerated stress tests in different potential regimes. In this context, P and S doped supports were found to exhibit a high degree of interaction with Pt, providing increased degradation resistance compared to N and non-doped support.
CRIS-Team Scopus Importer:2023-03-24

Dimethyl ether/CO2 - a hitherto underestimated H2 storage cycle - Schühle, Patrick; Stöber, Robert; Semmel, M.; Schaadt, A.; Szolak, R.; Thill, S.; Alders, M.; Hebling, C.; Wasserscheid, Peter; Salem, O. (Energy and Environmental Science, 2023)
Large amounts of renewable energy will have to be stored and transported in the future. For this task, chemical hydrogen storage technologies are particularly suitable. In this paper, we show that the DME/CO2 storage cycle is especially promising for point-to-point transport of renewable hydrogen over long distances. Surprisingly, this technology has been neglected so far, as DME has been mostly discussed as a fuel substitute for internal combustion engines while the back transport of CO2 has not been considered in this context. Our study reveals that the similarity of the physico-chemical properties of DME and CO2 enables back-shipping of CO2 after hydrogen release in the same vessel that is used to transport DME. This leads to an overall technology that shows in our analysis considerable potential to outperform ammonia or methanol, which are intensively discussed as hydrogen vectors today. The proposed cycle is characterised in particular by comparatively high energy efficiency, reduced mass flows per ton of delivered hydrogen, lower water consumption at the hydrogen production site and lower toxicological risks.
CRIS-Team Scopus Importer:2023-08-11

Effect of Conversion, Temperature and Feed Ratio on In2O3/In(OH)3 Phase Transitions in Methanol Synthesis Catalysts: A Combined Experimental and Computational Study - Kampe, Philipp; Wesner, Anne; Schühle, Patrick; Hess, Franziska; Albert, Jakob (ChemPlusChem, 2023)
Catalytic hydrogenation of CO2 to methanol has attracted lots of attention as it makes CO2 useable as a sustainable carbon source. This study combines theoretical calculations based on the dummy catalytic cycle model with experimental studies on the performance and degradation of indium-based model catalysts for methanol synthesis. In detail, the reversibility of phase transitions in the In2O3/In(OH)3 system under industrial methanol synthesis conditions are investigated depending on conversion, temperature and feed ratio. The dummy catalytic cycle model predicts a peculiar degradation behavior of In(OH)3 at 275 °C depending on the water formed either by methanol synthesis or the competing reverse water-gas-shift reaction. These results were validated by dedicated experimental studies confirming the predicted trends. Moreover, X-ray diffraction and thermogravimetric analysis proved the ensuing phase transition between the indium species. Finally, the validated model is used to predict how hydrogen drop out will affect the stability of the catalyst and derive practical strategies to prevent irreversible catalyst degradation.
CRIS-Team Scopus Importer:2023-09-22
Keywords: catalyst degradation; CO; dummy catalytic cycle; indium; methanol synthesis

Highly durable spray-coated plate catalyst for the dehydrogenation of perhydro benzyltoluene - Nathrath, Phillip; Raed Ramzi, Yousuf; Bierling, Markus; Thiele, Simon; Wasserscheid, Peter; Schühle, Patrick (Catalysis: Science and Technology, 2024)
In this study, we introduce a new spray coating technique to produce porous catalytic layers for the dehydrogenation of hydrogen carriers. The composition of the sol-gel composite dispersion is adjusted by a design of experiments (DoE) approach in order to reach excellent spraying processability, high coating stability, and a high coating load. In this way, coatings with remarkably high thicknesses of up to 500 μm, good durability, and decent adherence on stainless steel substrates were achieved. Furthermore, the precise adjustment of the coating loads and thicknesses of the highly porous γ-alumina catalyst support coating is demonstrated using the developed approach. Coating of different line-of-sight geometries, e.g., corrugated plates, is also shown. The coated plates have been impregnated with platinum and tested in the highly endothermic dehydrogenation of perhydro benzyltoluene. Scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDX) revealed an increasing penetration depth of platinum into the coating layer with higher platinum loadings. For the dehydrogenation reaction, high surface related productivities of 0.8 mgH2 min−1 cm−2 using a platinum loading of 3.7 wt% were reached, and the coatings proved completely mechanically stable under these hydrogen release conditions.
CRIS-Team Scopus Importer:2024-02-09

Highly Selective Synthesis of Methanol from Glucose in a Two‐Step Process - Haagen, Vera; Schörner, Markus; Albert, Jakob; Franken, Tanja; Schühle, Patrick (Chemie Ingenieur Technik, 2022)

Hydrogen production from wet biomass via a formic acid route under mild conditions - Kroll, Fabian; Schörner, Markus; Schmidt, Matthias; Kohler, Florian T.U.; Albert, Jakob; Schühle, Patrick (International Journal of Hydrogen Energy, 2024)
Renewable Hydrogen is a key building block for a sustainable energy economy. An attractive resource for its production is waste biomass. This contribution analyses a promising new Biomass-to-H2 two-step approach, consisting of (1) biomass oxidation to formic acid and methyl formate in the so-called OxFA-Process and (2) hydrogen generation by dehydrogenation or decarbonylation of these intermediates. This contribution explains a novel hydrogen production concept and compares three distinct process routes for their efficient implementation. By using Aspen Plus® V12 the process was designed and optimized to achieve maximum hydrogen yield. An economic analysis allowed to compare the different characteristics of each process concept and to select the most promising option. The chosen concept was subject to a detailed cost and sensitivity analysis showing that this new route has high potential and competitiveness for hydrogen production from waste biomass.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Biomass oxidation; Decentral production; Formic acid; Hydrogen; Technoeconomic analysis

Hydrogen release from liquid organic hydrogen carrier using plate catalysts in continuous and dynamic operation - Nathrath, Phillip; Baier, Benjamin; Herz, N; Wituschek, Simon; Raed Ramzi, Yousuf; Merklein, Marion; Li, M.; Lederle, F.; Wasserscheid, Peter; Hübner, E.G.; Schühle, Patrick (Chemical Engineering Journal, 2025)
Significant fluctuations in energy supply are anticipated with the increasing utilization of renewable energy sources. To mitigate these fluctuations, green hydrogen released from Liquid Organic Hydrogen Carrier (LOHC) systems offers a promising solution. The use of plate catalysts in novel continuous reactor configurations enables favorable heat and mass transfer rates to drive this highly endothermic hydrogen release reaction. These catalytic plate reactors facilitate dynamic operation modes for an effective response to rapid changes in hydrogen and energy demand. In this study the performance of an established spray-coated plate catalyst is tested for the first time in continuous and dynamic operation modes. In detail, the productivity in hydrogen release from the LOHC-molecule perhydro benzyltoluene (H12-BT) is determined using a catalytic plate reactor and a tailored restart protocol was developed to maintain high hydrogen release productivities after a reactor shutdown. The plate catalysts showed good activity of up-to 0.25 mgH2 min−1 cm−2, a highly dynamic response in hydrogen release and an excellent stability under stationary and fluctuating conditions. Furthermore, a novel non-additive manufacturing method for plate catalysts through laser-texturing is introduced. The morphology of these new structures is characterized and their dehydrogenation performance is compared to the superior spray-coated benchmark.
CRIS-Team Scopus Importer:2025-02-07
Keywords: Benzyltoluene; Dehydrogenation; Laser-texturing; LOHC; Plate reactor

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene† - Schörner, Markus; Solymosi, Thomas Andrew; Raczka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt–alumina on steel beads, b) Pt–alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with P
Keywords: Hydrogen storage; Inductive heating; LOHC; Platinum; Perhydro benzyltoluene

Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene - Schörner, Markus; Solymosi, Thomas; Razcka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt-alumina on steel beads, b) Pt-alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with Pt.
CRIS-Team Scopus Importer:2024-08-23

Influence of gas impurities on the hydrogenation of CO2to methanol using indium-based catalysts - Schühle, Patrick; Schmidt, Maximilian; Schill, Leonhard; Riisager, Anders; Wasserscheid, Peter; Albert, Jakob (Catalysis: Science and Technology, 2020)
In this study, the performance of an In2O3/ZrO2 catalyst for hydrogenation of CO2 to methanol is reported in the presence of typical impurities of industrial CO2 feed gas streams. Experiments were performed with defined amounts of SO2, H2S, NO2, NH3 and hydrocarbons purposely added to the reaction mixture under industrially relevant conditions (225-275 °C, 50 bar total pressure, H2 : CO2 = 3 : 1). Comparative studies-with and without added impurities-further relate the observed effects to the behaviour of the commercial Cu/ZnO/Al2O3 methanol catalyst under identical treatments. Elemental analysis was used to determine the amount of sulphur, nitrogen and carbon residing on the catalyst after poisoning and after methanol synthesis. Moreover, temperature programmed desorption (TPD), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS) allowed identifying potential catalyst poisons formed on the catalyst surface. This work discloses that H2S and SO2 impurities led to drastic deactivation of the In2O3/ZrO2 catalyst (due to indium sulfide and -sulphate formation), while NH3, NO2 and hydrocarbon impurities have no major effect on the methanol production.
CRIS-Team Scopus Importer:2020-11-27

Laser-Generated InOx/ZrO2Catalysts for CO2Hydrogenation: Role of in Situ Fragmentation and Ripening Control - Lau, Kinran; Schühle, Patrick; Liang, Shun Xing; De Kock, Florian; Albert, Jakob; Reichenberger, Sven (ACS Applied Energy Materials, 2021)
It is desirable to reduce the reliance on fossil fuels and to develop alternative methods to yield valuable chemicals. CO2 hydrogenation to methanol is a promising approach, where In2O3/ZrO2 catalysts have attracted increasing attention due to their high selectivity and stability. However, the activity of indium-based catalysts is very susceptible to the preparation method, which is typically wet impregnation. Here, we explore a laser-based synthesis route to prepare InOx/ZrO2 catalysts of varying indium size and load. The respective particle sizes were either adjusted by in situ fragmentation with a more (ns-VIS-laser) or less (ns-IR-laser) efficient laser wavelength or by using micromolar concentrations of phosphate as an electrostatic stabilizer. The InOx colloids were subsequently deposited onto ZrO2 Our results demonstrate that the pulsed laser ablation with ns-IR-laser pulses yielded larger ∼45 nm crystalline cuboid InOx supported on zirconia. The frequency-doubled ns-VIS-pulses on the other hand caused an augmented in situ fragmentation during ablation, which led to catalysts with spherical ∼14 nm InOx particles with a significantly higher degree of amorphousness. Further size quenching and increased amorphous content of the InOx nanoparticles were observed when micromolar concentrations of phosphates were additionally present during ablation. After supporting the InOx nanoparticles onto ZrO2, the laser-generated catalysts were found to perform equally well as their wet-chemically prepared counterparts for methanol synthesis in a slurry phase, although crystalline In species performed slightly better in the catalytic reaction. In conclusion, in situ fragmentation does not only provide opportunities for independent studies of size and composition but also ripening control and structural modifications such as amorphization.
CRIS-Team Scopus Importer:2021-10-29
Keywords: amorphous nanoparticles; laser ablation in liquid; methanol synthesis; size quenching; slurry reaction

Phosphorus-modification of Pt/Al2O3 catalysts improves dispersion and cycloalkane dehydrogenation activity - Ellert, Abelina; Herold, Felix; Rønning, Magnus; Hutzler, Andreas; Piccirilli, Luca; Janssens, Ton V.W.; Vennestrøm, Peter N.R.; Wasserscheid, Peter; Schühle, Patrick (Journal of Catalysis, 2024)
In this study, we demonstrate that phosphorus-modification of Pt/Al2O3 leads to sinter-stable catalysts with improved activity in the dehydrogenation of perhydro benzyltoluene, an attractive liquid organic hydrogen carrier. TEM images show that platinum nanoparticles are stabilized to a size below 1 nm by the P-modification procedure, while unmodified counterparts show considerable sintering after reduction at 600 °C. The modification procedure starts by a simple impregnation of Pt/Al2O3 with H3PO3, followed by a high temperature treatment above 550 °C. It is crucial to adjust the right P:Pt ratio to reach stabilization of all platinum nanoparticles and thereby high catalytic surface areas. In our dehydrogenation studies, a catalyst with the optimal molar P:Pt ratio of 1.8 shows a 18 % higher activity compared to the unmodified sample. Even after treating the catalyst at temperatures up to 900 °C, this activity boost remains. XPS and XRD measurements prove that Pt stays in its reduced elemental state, also after P-modification, which is essential for a good dehydrogenation activity. The phosphorus species act as an anchor for the Pt particles on the Al2O3 surface, reducing their mobility and preserving small nanoparticles.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Dehydrogenation; Doping; Heterogeneous catalysis; LOHC; Phosphorus

Photocatalytic methanol oxidation to formaldehyde in a continuous laboratory plant over Aeroxide P25 - Stubenrauch, Florian; Schörner, Markus; Bösmann, Andreas; Schühle, Patrick; Wasserscheid, Peter (Reaction Chemistry & Engineering, 2024)
We here report the photochemical synthesis of formaldehyde by gas phase methanol oxidation with oxygen in a sophisticated continuous laboratory setup. The commonly used benchmark photocatalyst Evonik Aeroxide P25 was applied in combination with a narrow peak UV-A LED light source. Prior to its use, the applied powder catalyst was immobilized with a simple spray coating technique to a steel plate support (300 mm × 130 mm × 20 mm). With this system, reaction engineering studies have been carried out to elaborate the dependencies of catalyst mass, irradiation, residence time and temperature on achieved conversions, selectivities, yields, reaction rates, and apparent quantum efficiencies. We found that catalyst load influences conversion in an extended plateau like manner. High irradiation and residence time benefit MeOH conversion while the selectivity for HCHO decreases with both parameters. Temperature showed an interesting influence, as it increases both conversion and selectivity, until desorption effects become dominating over 120 °C. Our work thus for the first time provides application relevant information for an industrial highly interesting reaction and a heavily researched model photocatalytic system that has so far been mainly studied under surface science conditions.
CRIS-Team Scopus Importer:2024-03-15

Site blocking effects on P-modified Pd/Al2O3 catalysts for LOHC hydrogenation: an in situ DRIFTS study - Sheng, Yaoci; Seitz, Adrian; Gambu, Thobani; Zhang, Kailun; Schühle, Patrick; Retzer, Tanja (Catalysis: Science and Technology, 2025)
In this paper, we investigate structural changes of a P-modified Pd/Al2O3 catalyst for the hydrogenation of liquid organic hydrogen carriers (LOHCs) e.g., benzyltoluene (H0-BT). We elucidate the effect of P modification on the Pd nanoparticles (NPs) and the support material via a systematic combination of reactor studies, in situ diffuse reflectance FT-IR spectroscopy using CO as a probe molecule (CO-DRIFTS), and density functional theory (DFT). We find that P modification induces structural changes as well as site-blocking effects on the Pd NPs. In particular, phosphates on the Al2O3 support induce the formation of smaller Pd NPs. Phosphate species further reside on the terrace sites of Pd NPs, which leads to competitive adsorption between phosphates and CO/H2 especially at the Pd(111) facet. This demonstrates rearrangement of surface and adsorbate species on the P-modified Pd/Al2O3 catalysts under reactive gas atmosphere.
CRIS-Team Scopus Importer:2025-05-09

Slurry Phase Hydrogenation of CO2 to Methanol Using Supported In2O3 Catalysts as Promising Approach for Chemical Energy Storage - Schühle, Patrick; Reichenberger, Sven; Marzun, Galina; Albert, Jakob (Chemie Ingenieur Technik, 2020)
A promising approach for chemical energy storage from fluctuating renewable electricity is methanol synthesis from CO2 and hydrogen in a slurry reactor concept, due to efficient heat storage and easy reactor control. In combination with a promising In2O3/ZrO2 catalyst and mineral oil as carrier liquid, efficient methanol production under a wide range of changing process conditions is shown for the first time. A maximum methanol productivity of 2.1 gMeOHgIn−1h−1 and multiple recycling stability of the catalyst and the carrier liquid was achieved, showing no significant decrease in methanol yields.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Carbon dioxide; Chemical energy storage; Indium catalyst; Methanol; Slurry reaction

Supported Ruthenium Phosphide as a Promising Catalyst for Selective Hydrogenation of Sugars - Popp, Lukas; Kampe, Philipp; Fritsch, Birk; Hutzler, Andreas; Poller, Maximilian J.; Albert, Jakob; Schühle, Patrick (European Journal of Inorganic Chemistry, 2024)
This work demonstrates that supported ruthenium phosphides (RuP2) are attractive catalysts for selective production of alditols by sugar hydrogenation. In our studies, carbon supported RuP2 with a ruthenium content of 5 wt.– % led to the highest activity in xylose hydrogenation and to nearly 100 % yield for xylitol. ICP-OES and XRD measurements revealed the stability of this novel RuP2/C catalyst under typical hydrogenation conditions (50 barH2, 120 °C) in aqueous phase. Furthermore, STEM-EDX illustrated the close proximity of ruthenium and phosphorous on the catalyst site and the formation of nanoparticles in the size of 2–4 nm. The catalyst system was successfully applied for the selective hydrogenation of further sugar substrates, including glucose, fructose, and disaccharides, such as cellobiose and sucrose. Here, the RuP2/C revealed its bifunctional acidic/metallic character, enabling in a tandem reaction the hydrolysis of disaccharides, directly followed by a selective hydrogenation to form sugar alcohols in high yield.
CRIS-Team Scopus Importer:2024-06-21
Keywords: ruthenium phosphide; selective hydrogenation; sugar alcohols; sugar hydrogenation; Transition metal phosphides

Synthesis of methanol by hydrogenolysis of biobased methyl formate using highly stable and active Cu-spinel catalysts in slurry and gas phase reactions - Haagen, Vera; Iser, Jakob; Schörner, Markus; Weber, Dennis; Franken, Tanja; Wasserscheid, Peter; Schühle, Patrick (Green Chemistry, 2023)
This contribution deals with a new atom efficient two-stage production route for green methanol (MeOH) from biomass that includes biomass conversion to methyl formate (MF)/formic acid (FA) mixtures followed by hydrogenolysis to MeOH. Herein, we focus on the hydrogenolysis step and propose a materials solution to the problem of catalyst corrosion by the acidic MF/FA mixture formed in the previous biomass oxidation step. We show that Cu0.9Al2O4 spinel materials are very effective hydrogenolysis catalysts for the conversion of MA/FA mixtures to MeOH. Compared to commercial catalysts such as CuO/Cr2O3, the spinel material does not contain hazardous chromium compounds or require them during synthesis. Furthermore, this spinel catalyst shows much lower corrosion than known commercial hydrogenolysis catalysts. By using reactive frontal chromatography, nitrogen sorption, IR-ATR and XRD measurements we show, that CuO/MgO/ZnO/Al2O3 and CuO/Cr2O3 suffer from leaching of copper and chromium in the presence of FA due to the formation of mobile metal formate species. In contrast, the strongly fixed nature of copper in the highly ordered crystal structure of our Cu0.9Al2O4 spinel type catalyst leads to exceptional stability in the presence of FA and in continuous hydrogenolysis experiments for more than 110 h time-on-stream.<br

Thermophysical properties of the energy carrier methanol under the influence of dissolved hydrogen - Kerscher, Manuel; Jander, Julius Hans; Luther, Fabian; Schühle, Patrick; Richter, Markus; Rausch, Michael Heinrich; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2023)
Keywords: Isochoric-saturation method; Methanol; Chemical hydrogen storage; Dynamic light scattering; Raman spectroscopy; Thermophysical properties

Tunable Photocatalytic Activity of PEO-Stabilized ZnO-Polyoxometalate Nanostructures in Aqueous Solution - Bernhardt, Sarah; Düring, Jasmin; Haschke, Sandra; Barr, Maissa; Stiegler, Lisa; Schühle, Patrick; Bachmann, Julien; Hirsch, Andreas; Gröhn, Franziska (Advanced Materials Interfaces, 2021)
The photocatalytic activity and selectivity of novel binary and ternary composite nanostructures from polyethylene oxide-stabilized zinc oxide (PEO-ZnO) with and without polyoxometalate (H-4[Si(W3O10)(4)], POM) are determined in aqueous solution under UV-light. Mono- and di-COOH-end-functionalized PEO polymers are used as surface modifiers, influencing the morphology and stability of the ZnO nanoparticles being synthesized in water. POM acts as an additional versatile photocatalytically active building block resulting in a ternary hybrid structure with tunable photocatalytic activity. Catalytic selectivity is demonstrated by studying photocatalytic dye degradations as model reactions, where the chemical backbone of the dyes and their charge turn out to be the basis for the selectivity. All samples are characterized with dynamic light scattering, transmission electron microscopy, scanning electron microscopy, light microscopy, and zeta-potential measurements. With the functionalized PEOs, large ZnO clusters consisting of leaves are formed while 2-[2-(2-methoxyethoxy) ethoxy] acetic acid (TODA) yields ZnO flower-like structures.
CRIS-Team WoS Importer:2021-07-09